2015
DOI: 10.1111/hiv.12241
|View full text |Cite
|
Sign up to set email alerts
|

Baseline prevalence and predictors of liver fibrosis among HIV‐positive individuals: a substudy of the INSIGHT Strategic Timing of AntiRetroviral Treatment (START) trial

Abstract: At baseline, significant liver fibrosis was observed in approximately 8% of participants, with higher ALT and HIV RNA the only clinical factors associated with increasing TE score. TE will be used annually to monitor fibrosis and evaluate the role of ART in further fibrosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
(45 reference statements)
5
17
3
Order By: Relevance
“…This was also similar to another study that included Botswana and South African pregnant women, and the baseline CD4 + T cells for Batswana were similar between the HIV/HBV-coinfected and HIV-monoinfected group, whereas that of South Africans were lower in the HIV/HBV-coinfected group [45]. Other studies in South Africa and Tanzania reported marginally lower baseline CD4 + T cells [17, 35].…”
Section: Discussionsupporting
confidence: 86%
“…This was also similar to another study that included Botswana and South African pregnant women, and the baseline CD4 + T cells for Batswana were similar between the HIV/HBV-coinfected and HIV-monoinfected group, whereas that of South Africans were lower in the HIV/HBV-coinfected group [45]. Other studies in South Africa and Tanzania reported marginally lower baseline CD4 + T cells [17, 35].…”
Section: Discussionsupporting
confidence: 86%
“…There were relatively few individuals in the study with HBV (2.8%) or HCV (3.7%) infections. However, overall fibrosis‐4 scores were less likely to rise >1.45 in those in the immediate compared to delayed ART groups, an effect that was evident 12 months after randomization and was persistent for 60 months . Thus, underlying liver disease caused by HCV, HBV, alcohol, or another condition is an additional reason to treat all individuals infected with HIV as soon as possible.…”
Section: Hiv Treatmentmentioning
confidence: 99%
“…These measures can be used individually or in validated composite scores such as the AST to Platelet Ratio Index (APRI) and Fibrosis‐4 Index (FIB‐4), which have been used as noninvasive markers of liver fibrosis in various populations . In a substudy of 221 START trial participants with transient elastography results, 7.8% had significant liver fibrosis, while higher ALT, higher HIV RNA, and Hispanic/Latino ethnicity were associated with higher elastography scores . In this study, our objective was to use APRI and FIB‐4 to determine the prevalence of and risk factors for liver fibrosis among START study participants at baseline and follow‐up and to assess for an effect of early versus delayed initiation of ART on progression of liver fibrosis over time.…”
mentioning
confidence: 99%